1923 N.D. Laws 380, ch. 266, § 5. - (:unkn) unknown (General Publisher, 1923)
Sec. 5. Aliens and Criminals Must Not Possess Arms. No unnaturalized foreign-born person and no person who has been convicted of a felony against the person or property of another or against the Government of the United States or of any State or subdivision thereof, shall own or have in his possession or under his control, a pistol or revolver. Violations of this section shall be punished by imprisonment for not to exceed five years.
--
Keywords: POSSESSION - DANGEROUS PERSONS